Implementing the Teams Games Tournament Model in Teaching Javanese Script Writing to Fourth-Grade Elementary School Students - Much Arsyad Fardani; Dwiana Asih Wiranti (Journal of Educational Learning and Innovation (ELIa), 2025)
This study aims to determine the improvement of Javanese script writing skills through the application of the Teams Games Tournament (TGT) learning model in fourth-grade students of Mranak 2 Elementary School. The study used a quantitative method with a Pre-Experimental One-Group Pretest–Posttest design. The subjects of this study were 24 fourth-grade students. Data collection techniques included interviews, observations, and written tests. Data analysis used the N-Gain Test carried out with the help of SPSS version 27. N-gain was used to measure the improvement of Javanese script writing skills. The results showed an N-Gain value of 0.6043, indicating an improvement in the moderate category. Thus, the TGT model can improve the Javanese script writing skills of fourth-grade elementary school students.